HIF-1α Pulmonary Phenotype Wide Association Study Unveils a Link to Inflammatory Airway Conditions - Kelchtermans, Jelte; Chang, Xiao; March, Michael E.; Mentch, Frank; Sleiman, Patrick M. A.; Hakonarson, Hakon (Frontiers in Genetics, 2021)
Despite experimental data linking HIF-1a dysfunction to inflammatory airway conditions, the effect of single nucleotide polymorphisms within the HIF1A gene on these conditions remains poorly understood. In the current study, we complete a phenotype wide association study to assess the link between SNPs with known disease associations and respiratory phenotypes. We report two SNPs of the HIF1A gene, the intronic rs79865957_G_A and the missense rs41508050_C_T. In these positions the A and the T allele are significantly associated with allergic rhinitis and acute bronchitis and bronchiolitis, respectively. These findings further support the role of HIF-1a in inflammatory pulmonary conditions and may serve as a basis to refine our understanding of other HIF-1a associated phenotypes.